Long-life proton exchange membrane with pyridine side group and preparation method of long-life proton exchange membrane
By introducing pyridine pendant groups into perfluoroion polymers to capture or quench free radicals, the problem of insufficient chemical stability of perfluorosulfonic acid proton membrane is solved, and the long life and efficient ion exchange of the polymer are achieved.
Patent Information
- Application Number
- CN202411398020.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2021-11-04
- Publication Date
- 2025-02-21
AI Technical Summary
The existing perfluorosulfonic acid proton membranes are susceptible to free radical erosion during use, resulting in insufficient chemical stability of the membrane and short service life.
Using perfluoroion polymers with pyridine pendant groups whose structural units include pyridine groups and perfluoroether structural units, the free radicals are trapped or quenched through the conjugated structure of the pyridine unit, thereby enhancing the free radicals. Chemical stability of polymers.
It effectively weakens or slows down the degradation of polymers, extends service life, and maintains the mechanical strength and thermal stability of polymers, meeting the requirements of high ion exchange capacity and chemical stability.
Smart Images

Figure CN119490610A_ABST
Abstract
Description
[0001] This application is a divisional application of the application numbered 202111300405.3, and the invention name is a class of perfluoroionic polymers with pyridine side groups and their synthesis methods and applications Technical Field
[0002] The invention belongs to the technical field of fluorine-containing polymer materials and relates to a long-life proton exchange membrane with pyridine side groups and a preparation method thereof. Background Art
[0003] Perfluorosulfonic acid ionomers (PFSIs) have an ultra-stable perfluorinated backbone skeleton - (CF2CF2) m -(CF2CF) n -, and the side chain is a perfluoroether structure with a sulfonic acid group as the terminal group. The bond energy of the CF bond is as high as 4.85×105J / mol, which is much higher than the general CH bond energy, so the CF bond is very stable. Therefore, PFSIs show ultra-high chemical and thermal stability. PFSIs are mainly a type of polymer functional material that can conduct and exchange ion groups. One of its important uses is the preparation of ion exchange membranes for use in the field of proton exchange membrane fuel cells.
[0004] As a key material for this type of clean energy technology, in addition to requiring PFSIs to have high ionic conductivity, its chemical stability is also a factor that must be considered, because the chemical stability of PFSIs directly determines the long-term operation life of the fuel cell. However, during the operation of the fuel cell, the -SO3H side group carried by PFSIs is easily attacked by hydroxyl radicals, and ultimately leads to zipper-like degradation of the polymer main chain. Therefore, improving the chemical stability of PFSIs is of great significance to the ultimate practical application of fuel cells.
[0005] Current research suggests that the chemically stable degradation process of PFSIs is mainly a "zipper-like" degradation of the main chain or side chain of the polymer membrane attacked by free radicals (HO·&HOO·), which ultimately leads to the overall degradation of the polymer. During the synthesis of perfluoropolymers, initiators will inevitably produce unstable groups such as -CF=CF2, -COOH, -CF2SO3H and -CF2H at the ends of the molecular chains, and chemical degradation often occurs at the ends of these non-completely fluorinated molecular chains with unstable groups. Hydroxyl radicals will attack these groups, leading to degradation reactions. At present, there are two main means to improve the chemical stability of polymers due to free radical attack:
[0006] (1) Inhibit the generation of free radicals during polymer application.
[0007] (2) Quench or capture the generated free radicals by optimizing the polymer structure.
[0008] Ramani et al. [The Journal of Physical Chemistry B, 2007, 111 (30), 8684-8690] added cerium oxide to the ion membrane to capture the free radicals in the system, thereby alleviating the attack on the ion membrane and increasing the chemical stability of the membrane. The results show that the ion membrane with the addition of cerium oxide has good chemical stability. Chinese patent document CN102479956A (CN201010566820.9) improves the chemical stability of the membrane by modifying the microscopic morphology of the proton exchange membrane. In addition, the effect of scavenging free radicals is achieved by adding small molecule additives such as phenol and hindered amine to the membrane. Although the above technology can partially solve the problem of free radical tolerance of the membrane, the above method first prepares the polymer into an ion membrane, and then adopts a post-treatment strategy for the ion membrane to resist the attack of free radicals, and does not take measures to quench or capture the generated free radicals at the source of the polymer and its synthesis process. The shortcomings of this type of method mainly include: 1) This type of method will cause the small molecule additives to be unevenly distributed in the membrane and easily aggregate. 2) Such added substances do not contain ionic groups, which will reduce the strength and conductivity of the membrane. 3) Small molecule additives will continue to degrade and lose during long-term use and cannot provide long-term protection. Summary of the invention
[0009] The present invention aims to solve the problem that the existing perfluorosulfonic acid proton membrane is corroded by free radicals during use, thus resulting in a short service life of the proton membrane, and provides a class of perfluoro ion polymers with pyridine side groups and a synthesis method and application thereof.
[0010] In order to achieve the above object, the present invention adopts the following technical solutions:
[0011] A type of perfluoroionic polymer with pyridine side groups, the structural unit of the polymer is shown in formula (I):
[0012]
[0013] Wherein, the structure of formula (I) comprises an A unit and a B unit: the A unit is a pyridine structural unit, which comprises a pyridine group M and a perfluoroether structural unit, and the B unit comprises an ionic group -SO3H and a perfluoroether structural unit;
[0014] In the structure of formula (I), m is an integer of 0-5, and n is an integer of 1-6; preferably, m is an integer of 0-3, and n is an integer of 1-3;
[0015] More preferably, m is an integer from 0 to 1, and n is 2;
[0016] In the structure of formula (I), x is an integer of 1 to 30, and x+y / (x+y+z)=0.05 to 0.80, y / (y+z)=0.20 to 0.60; y / (y+z) is defined as the grafting rate;
[0017] Preferably, x+y / (x+y+z)=0.15-0.40; y / (y+z)=0.20-0.40; more preferably, y / (y+z)=0.26-0.35;
[0018] The structural formula of the monomer reagent providing the pyridine group M in the polymer A unit is shown in II,
[0019]
[0020] At least one of the R1 to R5 groups contains -NH2, and the other groups are electron-withdrawing groups or electron-donating groups, and the other groups cannot be electron-withdrawing groups at the same time, and the number of electron-withdrawing groups is at most 3.
[0021] Preferably, the R1 to R5 groups are -NH2, -CH2NH2, -Ph (Ph represents a benzene ring), -PhNH2, -PhCOOH, -Cl, -O-CH3, -CH3, -H, -F, -Br, CH3CH2-, (CH3)2CH-, or (CH3)3C-.
[0022] Among them, the electron donating groups in the above groups include: -NH2, -CH2NH2, -Ph, -PhNH2, -PhCOOH, -O-CH3, -CH3, CH3CH2-, (CH3)2CH-, (CH3)3C-; the electron withdrawing groups include -F, -Br, -Cl; the electron withdrawing ability of the above electron withdrawing groups is ranked as follows: (-F>-Cl>-Br).
[0023] In the present invention, the electron-donating group is conducive to forming a conjugated system with the pyridine ring, and can combine with free radicals to extend the life of the perfluoro ion polymer. The position of each group has no effect on the grafting rate of the M group and the perfluorosulfonic acid polymer.
[0024] Preferably, the R1 to R5 are not all -NH2 at the same time; the number of -NH2 in R1 to R5 is at most 3.
[0025] Preferably, R1 is -NH2, -CH2NH2, -Ph (Ph represents a benzene ring), -PhNH2, -PhCOOH, -Cl, -O-CH3 or -CH3; R2 is -H, -NH2, -PhNH2, -F, -PhCOOH or -CH3; R3 is -H, -NH2, -PhNH2, -PhCOOH, -Br, -Ph or -CH3; R4 is -H, -NH2, -PhNH2, -PhCOOH, -Br, -Ph or -CH3; R5 is -H, -NH2, -PhNH2, -Br or -CH3.
[0026] Further preferably, R1 is -NH2, -PhNH2 or -H; R2 is -NH2, -H or -PhNH2; R3 is -NH2, -PhNH2 or -CH3; R4 is -NH2, -PhNH2 or -CH3; R5 is -H, -NH2 or -CH3.
[0027] In at least one preferred technical solution of the present invention, R1 is -NH2, and R2, R3, R4, and R5 are H.
[0028] In at least one preferred technical solution of the present invention, R1 is -CH2NH2, and R2, R3, R4, and R5 are H.
[0029] Preferably, the number average molecular weight of the perfluoro ion polymer of formula (I) is 200,000 to 1,000,000, preferably 200,000 to 600,000, and particularly preferably 300,000 to 500,000. The ion exchange capacity (IEC) of the perfluoro ion polymer is 1.03 to 1.50 mmol / g.
[0030] The polymer of the present invention has the following advantages: (1) retaining the ultra-stable advantageous unit of the perfluoropolymer - (CF2CF2) x -, ensuring sufficient mechanical strength and thermal stability of the polymer. (2) Chemical grafting is performed on the side chain terminal groups of the perfluorovinylsulfonyl fluoride resin, and the introduced functional pyridine structure can effectively capture or quench free radicals, thereby weakening or slowing down the degradation of the polymer. (3) The perfluoroionic polymer synthesized by the present invention can simultaneously meet the requirements of high ion exchange capacity (IEC) and strong chemical stability, and has a wide range of applications. The proportion of A units, i.e., the grafting rate (y / (y+z) is defined as the grafting rate) can be adjusted to synthesize perfluoroionic polymers (PFSIs) with ion exchange capacity IEC and chemical stability that meet various requirements.
[0031] Another object of the present invention is to provide a method for synthesizing a class of perfluoroionic polymers (PFSIs) with pyridine side groups, comprising the following steps:
[0032] (1) a perfluorosulfonyl fluoride resin (Formula III) is subjected to a one-step grafting reaction with a monomer reagent providing a pyridine group M in an organic solvent to synthesize an intermediate product with a pyridine side group (Formula IV);
[0033] The reaction process is shown in formula (1-1):
[0034]
[0035]
[0036] (2) The intermediate product obtained in step (1) is treated with alkali and acid to complete ion exchange, and the unreacted sulfonyl fluoride group (-SO2F) is converted into a sulfonic acid group (-SO3H). After washing and drying, a perfluoroionic polymer with pyridine side groups (Formula I) is obtained. The reaction process is shown in Formula (1-2).
[0037]
[0038] Preferably, the organic solvent in step (1) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dimethyl sulfoxide or ethyl acetate.
[0039] Preferably, in step (1), the molar ratio of the monomer reagent providing the pyridine group M to the perfluorosulfonyl fluoride resin (Formula III) is greater than 3, preferably 4 to 8:1.
[0040] Preferably, the mass volume ratio of the perfluorosulfonyl fluoride resin to the organic solvent in step (1) is 1:1 to 10, g / mL; more preferably 1:1 to 5, g / mL; most preferably 1:1 to 3, g / mL.
[0041] Preferably, the reaction temperature in step (1) is 15 to 150° C., preferably 25 to 100° C., and the reaction time is 1 to 48 hours, preferably 20 to 24 hours.
[0042] Preferably, the one-step grafting reaction of step (1) is: first dissolving the monomer reagent in an organic solvent, then adding perfluorovinyl sulfonyl fluoride resin for grafting reaction to synthesize an intermediate product with pyridine side groups, or first pre-swelling the perfluorovinyl sulfonyl fluoride resin in an organic solvent, and then adding the monomer reagent.
[0043] Further preferably, the pre-swelling in step (1) is: pre-swelling the perfluorovinylsulfonyl fluoride resin in an organic solvent at 40 to 80° C. for 60 to 100 minutes.
[0044] Further preferably, the grafting reaction in step (1) is as follows: placing an organic solvent in a container, adding a monomer reagent under stirring and nitrogen protection, slowly heating until the monomer reagent is completely dissolved, and then adding perfluorovinyl sulfonyl fluoride resin to react.
[0045] Preferably, the base in step (2) is one of sodium hydroxide and potassium hydroxide, with a concentration of 5 to 50 wt%, preferably 15 to 40 wt% of sodium hydroxide; the acid in step (2) is one of hydrochloric acid, sulfuric acid and nitric acid, with a concentration of 5 to 50 wt%, preferably 25 to 40 wt% of sulfuric acid or nitric acid.
[0046] Preferably, the washing in step (2) is performed by washing with deionized water multiple times, the drying temperature is 55 to 65° C., and the drying time is 18 to 36 hours.
[0047] The ion exchange capacity of the above-mentioned perfluoro ion polymer with pyridine side groups (Formula I) and the proportion of pyridine structural units can be determined by acid-base titration. The proportion of pyridine structural units can be controlled by adjusting the amount of monomer reagent added, reaction time and reaction temperature in step (1), that is, the grafting rate of the reaction is controlled, and then the ion exchange capacity of the perfluoro ion polymer is controlled.
[0048] The above-mentioned perfluoroionic polymer with pyridine side groups is used in one or more of the following applications: 1) in the manufacture of ion exchange membranes in fuel cells or electrolysis devices; 2) as a superacid in chemical catalysis; 3) in electrodialysis; 4) in seawater desalination; 5) in gas separation; 6) in the preparation of membrane electrodes for fuel cells; 7) in sewage treatment.
[0049] The present invention also provides a long-life proton exchange membrane, wherein the proton membrane component comprises the above-mentioned perfluoro ion polymer with pyridine side groups (Formula I).
[0050] A long-life proton exchange membrane for a fuel cell, wherein the structure of the proton exchange membrane is selected from one of the following:
[0051] 1) A proton exchange membrane prepared from the above-mentioned perfluoro ion polymer with pyridine side groups;
[0052] 2) A proton exchange membrane prepared from a mixture of the above-mentioned perfluoro ion polymer with pyridine side groups and a perfluorosulfonic acid polymer.
[0053] The above-mentioned preparation methods include spin coating, screen printing, dip coating, inkjet printing, solution casting and spray pyrolysis, etc., and the solution casting method is preferred.
[0054] Preferably, the ion conductivity of the proton exchange membrane is 80-120 mS / cm, the thermal degradation temperature is 280-305°C, and after 200 hours of Fenton test, the ion exchange capacity retention rate and ion conductivity retention rate are above 94%. Preferably, the thickness of the ion exchange membrane is 10-200 μm, and the ion exchange capacity of the proton exchange membrane is 1.03-1.50 mmol / g.
[0055] The long-life proton exchange membrane includes a membrane prepared entirely using the above-mentioned perfluoro ion polymer with pyridine side groups and a composite membrane prepared by adding the above-mentioned perfluoro ion polymer with pyridine side groups as a free radical quencher into a conventional perfluorosulfonic acid polymer.
[0056] The present invention also provides a method for preparing the long-life proton exchange membrane, wherein the perfluoro ion polymer (Formula I) with pyridine side groups is dissolved in an organic solvent to obtain a perfluoro ion polymer solution, and then a solution casting method is used to directly prepare a perfluorosulfonic acid proton exchange membrane;
[0057] Alternatively, the above-mentioned perfluoro ion polymer with pyridine side groups (Formula I) is added as a free radical quencher into a conventional perfluorosulfonic acid resin solution to obtain a perfluoro ion polymer composite solution, and a composite proton membrane is prepared by a solution casting method.
[0058] Preferably, the mass fraction of the perfluoro ion polymer solution is 5 to 35 wt %, more preferably 10 to 25 wt %.
[0059] Preferably, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate.
[0060] Further preferably, the volume ratio of ethanol to water in the ethanol / water mixed solvent is 8-9:1-2; the volume ratio of isopropanol to water in the isopropanol / water mixed solvent is 8-9:1-2.
[0061] Preferably, the mass proportion of the perfluoro ion polymer with pyridine side groups in the composite proton membrane is greater than or equal to 5%, and more preferably greater than or equal to 10%.
[0062] Preferably, the mass fraction of the perfluoro ion polymer composite solution is 5 to 30 wt %.
[0063] Preferably, the solution casting method comprises the following steps: coating a perfluoro ion polymer solution or a perfluoro ion polymer composite solution on a quartz surface dish, pre-drying at 80-90°C, drying at 140-150°C for 90-100 minutes, and removing the mold.
[0064] In the present invention, when preparing the composite proton exchange membrane, the ionic conductivity and chemical stability of the proton exchange membrane can be regulated by adjusting the proportion of the perfluoroionic polymer according to the requirements of product performance, thereby regulating the service life of the proton exchange membrane.
[0065] The present invention also provides a membrane electrode for a free radical resistant fuel cell with a long life span, wherein the catalyst mixture component of the catalyst layer of the membrane electrode comprises the above-mentioned perfluoro ion polymer with pyridine side groups.
[0066] A membrane electrode for an anti-free radical fuel cell consists of an electrode layer and a proton exchange membrane. The electrode layer includes a gas diffusion layer and a catalyst layer. The electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode. The proton exchange membrane is located between the hydrogen electrode and the oxygen electrode.
[0067] The proton exchange membrane may be the proton exchange membrane for fuel cells of the present invention or other conventional proton exchange membranes for fuel cells.
[0068] The method for preparing the membrane electrode for the above-mentioned free radical resistant fuel cell comprises the following steps:
[0069] (1) dissolving the above-mentioned perfluoro ion polymer with pyridine side groups in a water / alcohol mixed solvent to prepare a perfluoro ion polymer solution or adding the perfluoro ion polymer to a conventional perfluorosulfonic acid polymer solution to prepare a perfluoro ion polymer composite solution, then adding a platinum-based catalyst to the perfluoro ion polymer solution or the perfluoro ion polymer composite solution, and ultrasonically obtaining a membrane electrode slurry)
[0070] (2) using a spray gun to spray the membrane electrode slurry onto the hydrophobic gas diffusion layer to form a catalyst layer, and after heat treatment, an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained. The obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with the fuel hydrogen and oxygen in the membrane electrode;
[0071] (3) The hydrogen electrode and oxygen electrode cut to appropriate sizes are placed on the upper and lower sides of the proton exchange membrane, aligned and matched well, and then subjected to hot pressing to obtain a membrane electrode.
[0072] The gas diffusion layer (Gas Diffusion Layer) consists of a base layer and a microporous layer, wherein the base layer material is mostly porous carbon paper or carbon cloth, and the microporous layer is usually composed of conductive carbon black and a hydrophobic agent. The base layer is composed of a porous, non-woven carbon substrate with a macroporous structure. After the substrate is treated with PTFE hydrophobicity, a single or multi-layer microporous layer (MPL) is coated to form a porous structure with different pores.
[0073] According to the preferred embodiment of the present invention, the alcohol in the water / alcohol mixed solvent in step (1) is ethanol or isopropanol, and the volume ratio of water to alcohol is 1 to 2:8 to 9. The ultrasonic time is 30 to 200 min.
[0074] Preferably according to the present invention, the concentration of the perfluoro ion polymer in the perfluoro ion polymer solution or the perfluoro ion polymer composite solution in step (1) is 5 to 15 wt %.
[0075] According to the preferred embodiment of the present invention, the platinum loading of the catalyst layer in step (2) is 0.35-0.45 mg / cm 2 The heat treatment process in step (2) is 80-130° C. for 30-200 min.
[0076] Preferably, according to the present invention, the gas diffusion layer in step (2) is carbon paper treated with PTFE hydrophobicity.
[0077] Preferably, the proton exchange membrane in step (3) is the proton exchange membrane for fuel cells of the present invention or other conventional proton exchange membranes for fuel cells. Further preferably, the hot pressing process in step (3) is 0.1-5 MPa, the hot pressing temperature is 80-140°C, and the duration is 30-150s.
[0078] In the present invention, when preparing a membrane electrode for a fuel cell, the chemical stability of the membrane electrode for a fuel cell can be regulated by adjusting the proportion of the perfluoroionic polymer according to the requirements of product performance, thereby regulating the length of its service life.
[0079] One or more technical solutions provided by the specific embodiments of the present invention have at least the following beneficial effects compared to the proton membrane provided by the previously proposed methods for resisting or slowing down free radical attacks (CN 102479956, CN101281967A, CN 108878993 A):
[0080] (1) The ultra-stable advantageous unit of perfluoropolymer - (CF2CF2)x - is retained, ensuring that the polymer can simultaneously meet the requirements of mechanical strength (tensile strength greater than 20MPa), thermal stability (thermal degradation temperature greater than 200°C), and exchange capacity (greater than 0.9meq / g), and has high chemical stability and service life.
[0081] (2) Starting from the source of polymers, the present invention designs and synthesizes a type of perfluoroionic polymers containing functional pyridine structural units in the side chains, which can disperse or bind hydroxyl radicals through the conjugated structure of the pyridine units, thereby achieving the purpose of capturing or quenching free radicals, effectively weakening or slowing down the degradation of the polymer and extending the service life.
[0082] (3) By introducing active pyridine structural units into the structure of perfluoroionic polymers, the grafting rate can be adjusted by adjusting the amount of M group monomer reagent added, the reaction temperature and time; thereby, the ion exchange capacity and chemical stability of perfluoroionic polymers can be adjusted according to product requirements.
[0083] (4) The perfluoro ion polymer obtained in the present invention is obtained by grafting a functional group having the function of quenching or capturing free radicals onto a polymer side chain through a chemical reaction, and can be evenly distributed in the ion membrane, thus protecting the ion membrane stably and for a long time against the attack of free radicals.
[0084] (5) The polymer synthesized in the present invention has both ion conduction and free radical corrosion resistance.
[0085] (6) The present invention provides a membrane electrode for a free radical resistant fuel cell, which can effectively increase the service life of the membrane electrode.
[0086] (7) The perfluoroion polymer prepared by the present invention was subjected to a free radical decay test for 116 days ( Figure 1 ), the ion exchange capacity (IEC) retention rate is as high as 90% or more. The polymer can be used to prepare the corresponding ion exchange membrane, which has the function of resisting free radical attack. The prepared proton membrane is tested for free radical decay for 115 days ( Figure 2 ), the ion conductivity retention rate is as high as over 90%, which can effectively improve the service life of the perfluorosulfonic acid proton membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] Figure 1 The stability test results of the target product A2 described in Example 1;
[0088] Figure 2 The stability test results of the proton exchange membrane obtained in Example 1;
[0089] Figure 3 This is the infrared characterization result diagram of the target product A2 described in Example 1. DETAILED DESCRIPTION
[0090] The present invention is described in detail below in conjunction with specific embodiments, which are only used to illustrate the present invention in detail and are not used to limit the scope of the present invention. The present invention is not limited to the following embodiments, and other combination schemes derived from the present invention all belong to the protection scope of this patent.
[0091] In Examples 1-6, the polymer and proton membrane adopt Fenton test to accelerate the oxidation target product to achieve the purpose of investigating the chemical stability of the polymer and proton membrane. The chemical stability of the polymer and proton membrane is evaluated by testing the retention rate (RV%) of IEC before and after the Fenton test.
[0092] The specific conditions of the Fenton experiment are: 20ppm Fe 2+ Ions are added to 30wt% H2O2 to prepare Fenton's reagent. Then the polymer is immersed in Fenton's reagent in a water bath at 80℃. After a certain period of immersion, the IEC of the polymer is tested to determine the chemical stability of the polymer. In order to ensure the concentration of ·OH free radicals, the Fenton's reagent needs to be replaced every 3 hours.
[0093] Titration of ion exchange capacity IEC of polymer and proton membrane: accurately weigh a certain weight of dry polymer resin, then treat it in deionized water at 80℃ for 1h, and use a 1M NaCl aqueous solution for ion exchange for more than 12h. Collect the exchanged solution, use phenolphthalein as an indicator, and titrate with 0.1M NaOH standard solution until the solution turns pink. The IEC value of the polymer can be calculated according to the following formula:
[0094] IEC=(V NaOH ×C NaOH ) / m
[0095] Where:
[0096] V NaOH ——The volume of NaOH solution consumed, ml;
[0097] C NaOH ——molar concentration of NaOH solution, mmol / ml;
[0098] m——The mass of PFSA dry polymer resin, g.
[0099] Ion exchange capacity of polymer and proton membranes IEC retention rate:
[0100] RV%=(IEC1-IEC0) / IEC0
[0101] Wherein: IEC1 and IEC0 represent the IEC of the polymer before and after the Fenton test.
[0102] Proton membrane ion conductivity determination: The membrane resistance R was tested by two-electrode method, the instrument used was electrochemical workstation Autolab PGSTA302, the frequency range was 106Hz-10Hz, and the calculation formula was used
[0103] σ=L / RS to calculate conductivity;
[0104] Where:
[0105] L is the thickness of the membrane (cm), R is the resistance of the membrane (Ω), σ is the conductivity of the sample (S / cm), and S is the test area of the sample (cm 2).
[0106] Retention rate of proton membrane conductivity:
[0107] RV%=(σ1-σ0) / σ0
[0108] Where: σ1 and σ0 represent the ionic conductivity of the membrane before and after the Fenton experiment.
[0109] Thermal degradation temperature (defined as the temperature at which the polymer degrades by 5%): The test was conducted using a thermogravimetric analyzer, TAQ50 produced by Perkin Elmer, USA, with N2 atmosphere, a heating rate of 10° / min, and a temperature range of 50-800°C. The samples were dried at 60°C for 24 hours before testing.
[0110] Membrane electrode durability test:
[0111] The durability or chemical stability of the membrane electrode samples was evaluated at open circuit voltage (OCV) at 30% relative humidity (RH) and 90°C, with hydrogen and air gas flow rates of 3.43 slpm and 8.37 slpm, respectively. The OCV of each cell in the stack was monitored over time. When the OCV of any of the five cells in the stack reached 0.8 V or the H2Crosover was greater than 10 mA / cm 2 , end the test.
[0112] Example 1
[0113] A long-life perfluoro ion polymer containing pyridine groups, a proton membrane and a preparation method thereof, the specific implementation methods are as follows:
[0114] 4-Aminopyridine was selected as a reagent monomer providing a pyridine group M, and reacted with a perfluorosulfonyl fluoride resin (m=1, n=2, number average molecular weight of 400,000, x=10) to prepare a target proton membrane. The specific steps are as follows:
[0115] (1) After cleaning a 150 mL reaction kettle, 35 g of perfluorosulfonyl fluoride resin was added to 100 mL of N, N-dimethylformamide. The stirring device was turned on and the temperature was raised to 60°C and then pre-swelled for 60 minutes. After vacuuming and replacing with high-purity nitrogen three times, 0.05 g of 4-aminopyridine was added. After it was completely dissolved, it was slowly heated to 80°C for reaction. The molar ratio of perfluorovinylsulfonyl fluoride resin to 4-aminopyridine was about 1:6. After reacting at 80°C under mechanical stirring for 20 hours, it was cooled to room temperature. The product was filtered and washed with ethanol and deionized water for multiple times to remove unreacted 4-aminopyridine, and then dried to obtain an intermediate product, which was recorded as A1. The reaction process is as follows:
[0116]
[0117] (2) The polymer A1 obtained in step (1) was treated with 30 wt% sodium hydroxide and 25 wt% sulfuric acid at 80°C for 24 h to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) were converted into sulfonic acid groups (-SO3H). The product was washed with deionized water for multiple times and dried at 60°C for 20 h to obtain the target product, which was recorded as A2. The reaction formula is as follows:
[0118]
[0119] The IEC of the obtained target product A2 was 1.08 mmol / g after ion exchange capacity (IEC) measurement. In the structure of the obtained target product A2, y / y+z=0.26 (i.e., grafting ratio).
[0120] The target product A2 was tested by infrared transmission spectrum, and the test results were as follows: Figure 3 As shown, after the reaction, 1467cm -1 The characteristic peak of -SO2F disappeared completely, and the CH bond, the NH bond of the connecting group and -SO3 - The characteristic peaks are located at 1542 cm -1 , 1665 and 1053cm -1 Nearby; infrared results proved that the target product A2 has been successfully synthesized.
[0121] The stability of the target product A2 was tested by Fenton test. Figure 1 As shown, after 116 days of free radical decay test, the ion exchange capacity (IEC) retention rate is as high as more than 90%, which proves that the obtained perfluoro ion polymer has a high ability to resist free radical attack and can effectively improve the service life of the perfluoro ion polymer.
[0122] (3) The polymer target product A2 obtained in step (2) is dissolved in N,N-dimethylformamide to prepare a 15 wt% polymer solution, and then the solution is coated on a clean and smooth quartz surface dish, pre-dried at 80° C., placed in an oven at 145° C. for 90 minutes, taken out and demolded to obtain a long-life perfluorosulfonic acid proton membrane.
[0123] The ion conductivity of the proton exchange membrane in deionized water at 25°C is 102 mS / cm. The conductivity described in the present invention is measured under this condition. The stability of the proton exchange membrane was tested by Fenton test. The results are as follows: Figure 2 After 115 days of free radical decay test, the ion conductivity retention rate of the proton exchange membrane is as high as over 90%, which proves that the obtained proton exchange membrane has a high ability to resist free radical attack and can effectively improve the service life of the proton exchange membrane.
[0124] Example 2
[0125] A long-life perfluoro ion polymer containing pyridine groups, a proton membrane and a preparation method thereof, the specific implementation methods are as follows:
[0126] 4-Aminopyridine was selected as the monomer reagent of the M group to react with perfluorosulfonyl fluoride resin (m=0, n=2, number average molecular weight of 450,000, x=10) to prepare the target proton membrane. The specific experimental steps are as follows:
[0127] (1) After cleaning a 150 mL reactor, add 50 mL of N, N-dimethylformamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, add 0.05 g of 4-aminopyridine, slowly heat to 80°C, and add 30 g of perfluorosulfonyl fluoride resin after it is completely dissolved. The molar ratio of perfluorosulfonyl fluoride resin to 4-aminopyridine is about 1:8. After reacting at 80°C under mechanical stirring for 24 hours, cool to room temperature, filter the product, wash it with ethanol and deionized water for several times to remove unreacted 4-aminopyridine, and dry it to obtain an intermediate product, which is recorded as A3. The reaction process is as follows:
[0128]
[0129] (2) The intermediate product A3 obtained in step (1) was treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid at 80° C. for 24 h to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) were converted into sulfonic acid groups (-SO3H). The product was washed with deionized water for multiple times and dried at 60° C. for 18 h to obtain the target product, which was recorded as A4. The reaction process is shown below.
[0130]
[0131] The IEC of the obtained target product A4 was 1.50 mmol / g after ion exchange capacity (IEC) measurement. In the structure of the obtained target product A4, y / y+z=0.30.
[0132] (3) The target product A4 obtained in step (2) was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20wt% perfluoro ion polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid proton membrane. The ion conductivity of the above proton exchange membrane is 120mS / cm.
[0133] Example 3
[0134] A long-life perfluoro ion polymer containing pyridine groups, a proton membrane and a preparation method thereof, the specific implementation methods are as follows:
[0135] 4-Aminomethylpyridine was selected as the monomer reagent of the M group to react with perfluorosulfonyl fluoride resin (m=1, n=2, number average molecular weight of 420,000, x is 12) to prepare the target proton membrane. The specific experimental steps are as follows:
[0136] (1) After cleaning a 150 mL reactor, add 50 mL of N, N-dimethylacetamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, add 0.05 g of 4-aminomethylpyridine, slowly heat to 80°C, and add 45 g of perfluorosulfonyl fluoride resin after it is completely dissolved. The molar ratio of perfluorosulfonyl fluoride resin to 4-aminopyridine is about 1:4. After reacting at 80°C under mechanical stirring for 20 hours, cool to room temperature, filter the product, wash it with ethanol and deionized water for many times to remove unreacted 4-aminomethylpyridine, and dry it to obtain an intermediate product, which is recorded as A5. The reaction process is shown below.
[0137]
[0138] (2) The intermediate product A5 obtained in step (1) was treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid at 80° C. for 24 h to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) were converted into sulfonic acid groups (-SO3H). The product was washed with deionized water for multiple times and dried at 60° C. for 24 h to obtain the target product, which was recorded as A6. The reaction process is shown below.
[0139]
[0140] According to ion exchange capacity (IEC) measurement, the IEC of the obtained target product A6 is 1.03 mmol / g; in the structure of the obtained target product A6, y / y+z=0.35.
[0141] (3) The target product A6 obtained in step (2) was dissolved in a mixed solvent of ethanol / water (volume ratio = 9:1) to prepare a 15 wt% perfluoro ion polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80° C., placed in an oven at 145° C. for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid proton membrane. The ion conductivity of the above proton exchange membrane is 80 mS / cm.
[0142] The molar ratio of the monomer reagent providing the M group to the perfluorosulfonyl fluoride resin should be greater than 3 to ensure the smooth progress of the reaction.
[0143] Example 4
[0144] A long-life composite proton membrane for a fuel cell and a preparation method thereof, comprising the following steps:
[0145] (1) The target product A2 obtained in Example 1 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % perfluoro ion polymer solution A7.
[0146] (2) A perfluorosulfonic acid polymer (whose number average molecular weight is 450,000; ion exchange capacity is 1.05 mmol / g; structural formula is shown in Formula V below; a is 6) is dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt% perfluorosulfonic acid polymer solution A8.
[0147]
[0148] (3) Add solution A7 to solution A8 and mix them evenly by mechanical stirring, with the mass ratio of the two being 1:9. The resulting mixed solution is coated on a clean and smooth quartz surface dish, pre-dried at 80°C, and then placed in an oven at 145°C for 90 minutes, taken out and demolded, to prepare a long-life perfluorosulfonic acid composite proton membrane.
[0149] After measurement, the ion exchange capacity (IEC) of the obtained composite proton exchange membrane is 1.05 mmol / g; and the ion conductivity of the composite proton exchange membrane is 90 mS / cm.
[0150] In the composite proton membrane, the mass content of the perfluoro ion polymer A2 is 10%.
[0151] Example 5
[0152] A long-life composite proton membrane for a fuel cell and a preparation method thereof, comprising the following steps:
[0153] (1) The polymer A2 obtained in Example 1 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A9.
[0154] (2) The perfluorosulfonic acid polymer described in Example 4 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A10.
[0155] (3) Add the A9 solution to the A10 solution and mix them evenly by mechanical stirring, with the mass ratio of the two being 3:7. The obtained mixed solution is coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, and a pyridine-based long-life perfluorosulfonic acid composite proton exchange membrane is prepared.
[0156] The IEC measurement showed that the ion exchange capacity (IEC) of the obtained composite proton exchange membrane was 1.06 mmol / g. The ion conductivity of the composite proton exchange membrane was 95 mS / cm.
[0157] In the composite proton membrane, the mass content of the perfluoro ion polymer A2 is 30%.
[0158] Example 6
[0159] The preparation of a membrane electrode for a free radical resistant fuel cell comprises the following specific steps:
[0160] (1) The target product A2 in Example 1 was dissolved in a water / isopropanol (volume ratio of 2:8) mixed solvent to prepare a 5 wt% perfluoro ion polymer solution, and then 10 mL of the perfluoro ion polymer solution was added to a Pt / C catalyst, and ultrasonicated for 100 min to obtain a membrane electrode slurry, wherein the mass fraction of the perfluoro ion polymer in the obtained slurry was 5%;
[0161] (2) coating the perfluoro ion polymer solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, removing from the mold, and preparing a proton exchange membrane;
[0162] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , obtaining an electrode layer composed of a gas diffusion layer and a catalyst layer, wherein the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with the fuel hydrogen and oxygen in the membrane electrode; (4) placing the hydrogen electrode and the oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton exchange membrane (3 cm×3 cm) in step (2), aligning the upper and lower sides and matching them well, and subjecting them to hot pressing treatment with a press, the press pressure is 0.8 MPa, the hot pressing temperature is 140°C, the duration is 60 s, the press is opened, and the obtained membrane electrode for fuel cell is taken out after natural cooling.
[0163] Example 7
[0164] The preparation of a composite membrane electrode for a free radical resistant fuel cell comprises the following specific steps:
[0165] (1) A8 in Example 4 was diluted in a mixed solvent of water / isopropanol (volume ratio of 2:8), and then the target product A2 in Example 1 was added to form a composite solution, wherein the total polymer concentration in the composite solution was 5 wt %, and the proportion of A2 in the total polymer was 30 wt %; then 10 mL of the mixed solution was added with a Pt / C catalyst, and ultrasonicated for 150 min to obtain a membrane electrode slurry, wherein the mass fraction of the polymer in the obtained slurry was 5%;
[0166] (2) coating the composite solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, taking out and demolding, thereby preparing a composite proton exchange membrane;
[0167] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0168] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the composite proton exchange membrane (3 cm×3 cm) prepared in step (2), align them up and down and make sure they fit together perfectly, and then heat-press them using a press with a pressure of 0.8 MPa and a temperature of 140°C for 60 seconds. Open the press, cool naturally, and take out the resulting composite membrane electrode for fuel cells.
[0169] Comparative Example 1
[0170] The proton exchange membrane was prepared using unmodified perfluorosulfonic acid polymer as raw material. The perfluorosulfonic acid ion polymer (same as described in Example 4) was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20wt% polymer solution A8 without adding any additives. The obtained mixed solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, and removed from the mold to prepare a perfluorosulfonic acid proton membrane. The ion conductivity of the proton exchange membrane was 85mS / cm.
[0171] Comparative Example 2
[0172] The membrane electrode is prepared using unmodified perfluorosulfonic acid polymer as raw material, and the specific steps are as follows:
[0173] (1) The perfluorosulfonic acid polymer solution A8 of Example 4 was diluted in a mixed solvent of isopropanol / water (volume ratio of 8:2) to prepare a 5 wt% perfluorosulfonic acid polymer solution, and then 10 mL of the perfluorosulfonic acid polymer solution was added to a Pt / C catalyst and ultrasonicated for 100 min to obtain a membrane electrode slurry; the mass fraction of the unmodified perfluorosulfonic acid polymer in the obtained slurry was 5%;
[0174] (2) coating a 5 wt % perfluorosulfonic acid polymer solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 80 minutes, removing the solution from the mold, and preparing a perfluorosulfonic acid proton exchange membrane;
[0175] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , an electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0176] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton exchange membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly, and then process them by hot pressing with a press. The press pressure is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 seconds. Open the press, and take out the obtained membrane electrode after natural cooling.
[0177] Comparative Example 3
[0178] A composite proton membrane for a fuel cell and a preparation method thereof, wherein 4-aminopyridine is directly used as an additive for the proton exchange membrane without chemically grafting with a perfluoro ion polymer, and specifically comprises the following steps:
[0179] 4-aminopyridine was directly added as an additive to the perfluorosulfonic acid polymer solution A8, and the mixture was uniformly mixed by mechanical stirring. The molar ratio of the perfluorosulfonic acid polymer to 4-aminopyridine in the mixed solution was about 1:6. The obtained mixed solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded, and a proton exchange membrane was prepared.
[0180] After measurement, the ion exchange capacity (IEC) of the obtained composite proton exchange membrane is 0.72 mmol / g. The ion conductivity of the composite proton exchange membrane at room temperature (25° C.) is 52.5 mS / cm.
[0181] Comparative Example 4
[0182] A preparation method of a membrane electrode directly uses 4-aminopyridine as an additive component of the membrane electrode, and the specific steps are as follows:
[0183] (1) A8 in Example 4 was diluted in a water / isopropanol (volume ratio of 2:8) mixed solvent to a concentration of 5 wt %, and then 4-aminopyridine was added to prepare a perfluoro ion polymer composite solution, wherein the molar ratio of perfluorosulfonic acid polymer to 4-aminopyridine in the composite solution was about 1:6, and then 10 mL of the composite solution was added with a Pt / C catalyst, and ultrasonicated for 150 min to obtain a membrane electrode slurry;
[0184] (2) coating the perfluoro ion polymer composite solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, taking out and demolding, thereby preparing a proton exchange membrane;
[0185] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130° C. for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 ,
[0186] An electrode layer consisting of a gas diffusion layer and a catalyst layer is obtained, and the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode due to the difference in contact with fuel hydrogen and oxygen in the membrane electrode;
[0187] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton exchange membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly, and then perform hot pressing on them with a press. The press pressure is 0.8 MPa, the hot pressing temperature is 140°C, and the duration is 60 seconds. Open the press, cool naturally, and then take out the prepared membrane electrode.
[0188] The perfluoro ion polymer, proton exchange membrane and membrane electrode prepared above were tested for performance, and the results are shown in Tables 1 to 3:
[0189] Table 1. Chemical stability test results of perfluoroionomers
[0190]
[0191] After being tested by Fenton test for 200 hours, the IEC of the perfluoro ion polymer prepared by the present invention is above 94%, and the thermal degradation temperature is above 300°C. Compared with the unmodified perfluorosulfonic acid polymer, the IEC retention rate and thermal degradation temperature are significantly improved. This indicates that the perfluoro ion polymer with pyridine side groups prepared by the present invention has high chemical stability, weakens or slows down the degradation of the polymer, and has sufficient thermal stability.
[0192] Table 2. Performance test results of proton exchange membrane
[0193]
[0194]
[0195] The proton exchange membrane prepared by the perfluoro ion polymer with pyridine side groups of the present invention has an ion conductivity retention rate of more than 94% after being tested by the Fenton test for 200 hours, and the thermal degradation temperature of the proton exchange membrane is more than 290°C; the composite proton exchange membrane prepared by the perfluoro ion polymer with pyridine side groups of the present invention has an ion conductivity retention rate of more than 94% after being tested by the Fenton test for 200 hours, and the thermal degradation temperature of the composite proton exchange membrane is more than 280°C; compared with the proton exchange membrane prepared by the perfluorosulfonic acid polymer without modification (Comparative Example 1), the chemical stability and thermal stability of the proton exchange membrane of the present invention are significantly improved, and the service life of the proton exchange membrane is effectively extended.
[0196] Table 3. Performance test results of membrane electrode
[0197] Example 6 Example 7 Comparative Example 2 Comparative Example 4 Duration (h) 200.5 230.5 120.7 75.3
[0198] The membrane electrode prepared by the perfluoroionic polymer with pyridine side groups of the present invention can last for more than 200 hours at open circuit voltage (OCV), 30% relative humidity (RH) and 90°C, while the membrane electrode prepared by the unmodified perfluorosulfonic acid polymer (Comparative Example 2) lasts only 120.7 hours. It shows that the durability of the membrane electrode prepared by the present invention has been effectively improved. Comparative Example 3 is to directly add 4-aminopyridine to the unmodified perfluorosulfonic acid polymer to prepare a proton exchange membrane. Since small molecules are easy to agglomerate and lose, and do not contain ionic groups, the compatibility is poor, which leads to a decrease in its mechanical properties and conductivity, which in turn affects its service life.
Claims
1. A long-life proton exchange membrane with pyridine side groups, characterized in that The components of the proton exchange membrane include a perfluoro ion polymer with a pyridine side group, and the structure of the perfluoro ion polymer is shown in formula (I): Wherein, the structure of formula (I) comprises an A unit and a B unit: the A unit is a pyridine structural unit, which comprises a pyridine group M and a perfluoroether structural unit, and the pyridine group M and the perfluoroether structural unit are connected by "-NH-SO2-"; the B unit comprises an ionic group -SO3H and a perfluoroether structural unit; In the structure of formula (I), m is an integer of 0-5, and n is an integer of 1-6; In the structure of formula (I), x is an integer of 1 to 30, and (x+y) / (x+y+z)=0.05 to 0.80, y / (y+z)=0.20 to 0.60; The structural formula of the monomer reagent providing the pyridine group M in the A unit is shown in II, At least one of the R1 to R5 groups contains -NH2, and the other groups are electron-withdrawing groups or electron-donating groups, and the number of electron-withdrawing groups does not exceed 3.
2. The long-life proton exchange membrane with pyridine side groups according to claim 1, characterized in that: m is an integer of 0 to 3, and n is an integer of 1 to 3; preferably, m is an integer of 0 to 1, and n is 2. Preferably, (x+y) / (x+y+z)=0.15 to 0.40; y / (y+z)=0.20 to 0.
40. Preferably, the number average molecular weight of the perfluoro ion polymer formula is 200,000 to 1,000,000, preferably 200,000 to 600,000, and more preferably 300,000 to 500,000.
3. The long-life proton exchange membrane with pyridine side groups according to claim 1, characterized in that: R1 to R5 groups are independently -NH2, -CH2NH2, -Ph, -PhNH2, -PhCOOH, -Cl, -O-CH3, -CH3, -H, -F, -Br, CH3CH2-, (CH3)2CH-, or (CH3)3C-; Preferably, the R1 to R5 are not all -NH2; the number of -NH2 in R1 to R5 is at most 3; Preferably, R1 is -NH2, -CH2NH2, -Ph, -PhNH2, -PhCOOH, -Cl, -O-CH3 or -CH3; R2 is -H, -NH2, -PhNH2, -F, -PhCOOH or -CH3; R3 is -H, -NH2, -PhNH2, -PhCOOH, -Br, -Ph or -CH3; R4 is -H, -NH2, -PhNH2, -PhCOOH, -Br, -Ph or -CH3; R5 is -H, -NH2, -PhNH2, -Br or -CH3; Further preferably, R1 is -NH2, -PhNH2 or -H; R2 is -NH2, -H or -PhNH2; R3 is -NH2, -PhNH2 or -CH3; R4 is -NH2, -PhNH2 or -CH3; R5 is -H, -NH2 or -CH3; In at least one preferred technical solution of the present invention, R1 is -NH2, and R2, R3, R4, and R5 are H; In at least one preferred technical solution of the present invention, R1 is -CH2NH2, and R2, R3, R4, and R5 are H.
4. The long-life proton exchange membrane with pyridine side groups according to any one of claims 1 to 3, characterized in that: The synthesis method of the perfluoroion polymer comprises the following steps: (1) a perfluorosulfonyl fluoride resin as shown in formula III is subjected to a one-step grafting reaction with a monomer reagent providing a pyridine group M in an organic solvent to synthesize an intermediate product with a pyridine side group as shown in formula IV, The reaction process is shown in formula (1-1): (2) The intermediate product obtained in step (1) is treated with alkali and acid to complete ion exchange, and the unreacted sulfonyl fluoride group (-SO2F) is converted into a sulfonic acid group (-SO3H). After washing and drying, a perfluoroionic polymer with a pyridine side group as shown in the structure of formula (I) is obtained. The reaction process is shown in formula (1-2):
5. The long-life proton exchange membrane with pyridine side groups according to any one of claims 1 to 3, characterized in that: The ion conductivity of the proton exchange membrane is 80-120 mS / cm, the thermal degradation temperature is 280-305°C, and after 200 hours of Fenton test, the ion exchange capacity retention rate and ion conductivity retention rate are above 94%. Preferably, the thickness of the ion exchange membrane is 10-200 μm, and the ion exchange capacity of the proton exchange membrane is 1.03-1.50 mmol / g.
6. The method for preparing a long-life proton exchange according to any one of claims 1 to 5, characterized in that: The perfluoro ion polymer with pyridine side groups is dissolved in an organic solvent to obtain a perfluoro ion polymer solution, and then a proton exchange membrane is directly prepared by a solution casting method; Alternatively, a perfluoro ion polymer with a pyridine side group is added as a free radical quencher to a perfluorosulfonic acid resin solution to obtain a perfluoro ion polymer composite solution, and a composite proton exchange membrane is prepared by a solution casting method.
7. The preparation method according to claim 6, characterized in that: The mass fraction of the perfluoro ion polymer solution is 5 to 35 wt %, more preferably 10 to 25 wt %. Preferably, the mass fraction of the perfluoro ion polymer composite solution is 5 to 30 wt %.
8. The preparation method according to claim 6, characterized in that: The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate. Preferably, the volume ratio of ethanol to water in the ethanol / water mixed solvent is 8-9:1-2; the volume ratio of isopropanol to water in the isopropanol / water mixed solvent is 8-9:1-2.
9. The preparation method according to claim 6, characterized in that: The mass proportion of the perfluoro ion polymer with pyridine side groups in the composite proton membrane is greater than or equal to 5%, and more preferably greater than or equal to 10%.
10. The preparation method according to claim 6, characterized in that: The solution casting method comprises the following steps: coating a perfluoro ion polymer solution or a perfluoro ion polymer composite solution on a quartz surface dish, pre-drying at 80-90° C., drying at 140-150° C. for 90-100 minutes, and removing the mold.
Citation Information
Patent Citations
Oxidation resistance degradation composite roton switching membrana for fuel cell as well as preparation thereof
CN101281967A
Method for improving chemical stability of proton exchange membrane
CN102479956A
Method for reducing electrochemical degradation of proton exchange membrane
CN108878993A